Study of some abnormalities of ovule development to seed in Pistacia vera L. - Najmeh Hosseini (Zīst/shināsī-i Giyāhī-i Īrān, 2014)
Seed production in some crops like pistachio is limited by some abnormalities in ovule development stages. In this study, the ovule developmental stages as well as abnormalities of these stages were investigated. Pistacia vera ovule is single, fullynucellate, monotegumental and converse (anatrope) and is set in an ovary with basic placement and the Polygonum type embryo sac is organized in it one week after complete dehiscence. After pollination and fertilization of egg cell, after 6 weeks of complete dehiscence, the pericarpe was grown to final size and even the lignifications of endocarpe started but the zygote cell was in a dormant state and in 6-8 weeks after complete dehiscence the zygote cell division along an increase in endosperm division occured so that cotyledonary embryo was formed in 10-12 weeks after complete dehiscence and the cotyledons attained their final size in 3 weesks after that, namely 15 weeks after complete dehiscence and at this time, the seedless and filled fruits were completely distinguished. During the ovule development stages, some abnormalities were observed such as lack of embryo sac formation, embryo sac degeneration, small and abnormal embryo sac formation, vascular band collapse inside the funicule, presence of zygote without endosperm and presence of endosperm without zygote, and these abnormalities caused lack of enough ovule growth and seedless or semiseedless fruit formation in pistachio.